2009
DOI: 10.1063/1.3251786
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-resolution imaging of size-selected platinum clusters on TiO2(110) surfaces

Abstract: Size-selected Pt(n) (n=4,7-10,15) clusters were deposited on TiO(2)(110)-(1x1) surfaces and imaged at atomic resolution using an ultrahigh-vacuum scanning tunneling microscope with a carbon nanotube tip. Clusters smaller than Pt(7) lay flat on the surface with a planar structure and a planar-to-three-dimensional transition occurred at n=8 for Pt(n) clusters on TiO(2). However, both Pt(8) and Pt(9) had two types of geometric structures. The geometric structures depend strongly on the number of atoms in the depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 25 publications
8
50
1
Order By: Relevance
“…36 Most of the Pt 7 clusters are also one atomic layer high; however, there is a clear tail toward double-layer height that is absent for Pt 3 . Pt 10 clusters have a symmetric histogram centered at double-layer height, with equal weights on single-and triple-layer apparent heights.…”
Section: ■ Resultsmentioning
confidence: 99%
“…36 Most of the Pt 7 clusters are also one atomic layer high; however, there is a clear tail toward double-layer height that is absent for Pt 3 . Pt 10 clusters have a symmetric histogram centered at double-layer height, with equal weights on single-and triple-layer apparent heights.…”
Section: ■ Resultsmentioning
confidence: 99%
“…From a STM observation [1,2] for this system, it has been confirmed that the cluster structure for the number of Pt atoms, n ≤ 7, consists of single atomic layer of Pt (two dimensional (2D) cluster), however, two atomic layers of Pt (three dimensional (3D) cluster) for n ≥ 8. When such size selected Pt clusters on the substrate was tentatively observed by RHEED, the intensity distribution like a Debye-Sherrer ring pattern was very weakly observed.…”
Section: Introductionmentioning
confidence: 66%
“…New technology which forms size selected nano clusters with several numbers of Pt atoms has been developed [1,2]. Simultaneously, structure evaluation of such nano clusters is also required.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution UHV-STM images of size-selected Pt(n) (n=4,7-10,15) clusters deposited on TiO 2 (110)-(1x1) surfaces were obtained using a CNT tip (Fig. 15) [65]. Clusters ofstructures of the top layers.…”
Section: (A) Mechanical Attachment Methodsmentioning
confidence: 99%